A High‐Energy Aqueous Sodium‐Ion Capacitor with Nickel Hexacyanoferrate and Graphene Electrodes. Issue 12 (19th September 2017) - Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Sahoo, Surjit; Lim, Jong Hwan; Choi, Kyung Hyun; Kim, Sang Jae
Abstract: Sodium‐ion capacitors have received much attention compared to lithium‐based systems, owing to the improved safety and earth abundancy. Here, we assembled an aqueous sodium‐ion capacitor by using nickel hexacyanoferrate and graphene as positive and negative electrodes, respectively, in 1 M Na2 SO4 electrolyte. The fabricated capacitor can work in a wide potential window from 0 to 2 V, giving an energy density of 39.35 Wh kg −1 with better capacitance retention of about 91 %, even after 2000 cycles. Besides, the cost‐effective precursors as well as environmentally friendly and earth‐abundant electrolytes with high safety will ensure that the fabricated sodium‐ion capacitor system is suitable for next‐generation energy storage applications. Abstract : Under construction : An aqueous sodium‐ion hybrid capacitor using nickel hexacyanoferrate and graphene electrodes is constructed and the electrochemical performances are examined with neutral electrolyte.